2020
DOI: 10.1039/d0dt02583f
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence behaviour of Au(i)–Cu(i) heterobimetallic coordination polymers based on alkynyl-tris(2-pyridyl)phosphine Au(i) complexes

Abstract: A set of alkynyl-tris(2-pyridyl)phosphine Au(I) complexes was synthesized and characterized. Free coordination functions on the ligand environment periphery, namely ‘scorpionate’ PPy3 and C≡C bond, allowed these ditopic metalloligands to be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…Here, a wide range of luminescent gold­(I) complexes have been synthesized and their photophysical parameters have been thoroughly studied. They include planar three-coordinate complexes. In this regard, the photoluminescence properties of three-coordinate complexes 1 – 5 were studied.…”
Section: Resultsmentioning
confidence: 99%
“…Here, a wide range of luminescent gold­(I) complexes have been synthesized and their photophysical parameters have been thoroughly studied. They include planar three-coordinate complexes. In this regard, the photoluminescence properties of three-coordinate complexes 1 – 5 were studied.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have been used as precursors to obtain heterometallic clusters by the coordination of Cu­(I) in the chemical structure. As is known, both the N-atom in the phosphane ligand and the alkynyl moiety may coordinate with the copper­(I) metal centers and provide ancillary support to bimetallic cluster formation, thanks to the additional expected coordination to the Au­(I) atoms (Au­(I)···Cu­(I) weak contacts). ,, The obtained heterometallic complexes have been studied as red phosphorescence emitters and singlet oxygen photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…4−6 This type of bond occurs in all areas of gold chemistry, especially in catalysis 7 and photoluminescence. 8,9 Complexes containing P-donor ligands occupy a prominent place in gold(I) coordination chemistry, and many structurally characterized examples feature the expected Au(I)−Au(I) bonds. 10,11 It has been found that even coordination compounds with an extended ligand framework assemble in the solid state in such a way that the Au(I)−Au(I) bonds can contribute to overall stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most reports of metal–metal bonding deal with the solid state, where X-ray diffraction (XRD) structural parameters provide accurate information about metal–metal distances to reveal short ones. Such short distances are often observed in gold­(I) complexes, generally referred to as Au­(I)–Au­(I) bonding. This type of bond occurs in all areas of gold chemistry, especially in catalysis and photoluminescence. , Complexes containing P-donor ligands occupy a prominent place in gold­(I) coordination chemistry, and many structurally characterized examples feature the expected Au­(I)–Au­(I) bonds. , It has been found that even coordination compounds with an extended ligand framework assemble in the solid state in such a way that the Au­(I)–Au­(I) bonds can contribute to overall stability.…”
Section: Introductionmentioning
confidence: 99%